Factors affecting sukuk market development: empirical evidence from sukuk issuing economies - Aman, A. (Emerald Group Holdings Ltd., 2021)
Purpose: Both developed and developing countries, Muslim and non-Muslim, have been showing keen interest in sukuk financing. This interest was because of the lesson learned by both Asian and non-Asian economies that having a developed capital market is very essential to enable an economy resilient to the financial crisis. Therefore, this study aims to produce theoretical relationships and identify empirical support for the determinants of sukuk market development. Design/methodology/approach: By using panel data analysis, the study covers the period from 1993 until 2017, and includes 13 sukuk issuing economies as per the availability of data. Findings: The findings of the study revealed that the stage of economic development, banking system, money supply and current account balance are positively associated with sukuk market. Interestingly, economic size and exports appear to be negatively associated with sukuk. Practical implications: To flourish the domestic sukuk market, authorities need to strengthen the existing financial system and economic development. Originality/value: The study contributes in a limited body of knowledge on determinants of sukuk market development by exploring novel determining factors of foreign capital inflows as well as macroeconomic and financial factors. Â© 2021, Emerald Publishing Limited.